2017
DOI: 10.1371/journal.pcbi.1005536
|View full text |Cite
|
Sign up to set email alerts
|

A predictive coding account of bistable perception - a model-based fMRI study

Abstract: In bistable vision, subjective perception wavers between two interpretations of a constant ambiguous stimulus. This dissociation between conscious perception and sensory stimulation has motivated various empirical studies on the neural correlates of bistable perception, but the neurocomputational mechanism behind endogenous perceptual transitions has remained elusive. Here, we recurred to a generic Bayesian framework of predictive coding and devised a model that casts endogenous perceptual transitions as a con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(155 citation statements)
references
References 43 publications
12
133
2
1
Order By: Relevance
“…117 Conversely, PP provides a satisfying explanation of these copious backward connections, impugning their consignment to mere recurrent modulations in feedforward schema. 183,206 The explanatory power of this framework, exemplified in simulations of PP that readily account for phenomena ranging from V1 neuron response properties 207 to bistable perception 29 to perceptual illusions, 30,31 has led some to argue that everything the brain does can ultimately be explained in terms of prediction error minimization. 9,17,32 Such a bold contention has inevitably drawn skepticism, much of which has centered on the theory's empirical foundation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…117 Conversely, PP provides a satisfying explanation of these copious backward connections, impugning their consignment to mere recurrent modulations in feedforward schema. 183,206 The explanatory power of this framework, exemplified in simulations of PP that readily account for phenomena ranging from V1 neuron response properties 207 to bistable perception 29 to perceptual illusions, 30,31 has led some to argue that everything the brain does can ultimately be explained in terms of prediction error minimization. 9,17,32 Such a bold contention has inevitably drawn skepticism, much of which has centered on the theory's empirical foundation.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has been made, 4,42,162 the neurophysiological mechanisms responsible for the extraction of regularities and the generation of experience-based priors are not well understood. Although a range of candidate neural regions have been implicated in tracking a variety of sensory regularities and issuing predictions 29,37,40,53,55,75,120,144,158,162 (see Ref. 41 for a recent review), their precise relationships to the modulations observed in sensory processing are not yet established.…”
Section: Evidence Of Prediction In Sensory Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan and Craver 2011b) at present, pitched largely at Marr's (1982) "algorithmic" level of description with only tentative proposals about how the functional roles it identifies are realised in cortical circuitry (cf. Brodski et al 2015;Gordon et al 2017;Weilnhammer et al 2017). 6 Nevertheless, it nicely illustrates the points we are making, and manifests how a regulative and thoroughly predictive perspective on brain function harmonises with an iconic approach to cognitive representation.…”
Section: Homeostatic Prediction Machinesmentioning
confidence: 93%
“…With multistable stimuli however, information conveyed by a constant stimulus is sufficiently uncertain to evoke spontaneous alternations in conscious perception (Rubin, 1921;Boring, 1930;Necker, 1832), suggesting the decision process itself is hidden, with only the outcome made available to the agent. Crucially, ambiguous perception does not rely on dominance time as an index of uncertainty (Brascamp et al, 2005), as switches arise in a stochastic manner., Bi-stable figures have recently been studied in predictive-coding frameworks where perceptual transitions (see also : Dayan, 1998;Hohwy et al, 2008) correlated with anterior insulae and inferior frontal gyrii responses (Weilnhammer et al, 2017), regions also associated with economic uncertainty (Platt & Huettel, 2008;Grinband et al, 2006;Brevers et al, 2015;Preuschoff et al, 2008a;Mohr et al, 2010).…”
Section: Introductionmentioning
confidence: 99%